2018
DOI: 10.1097/tp.0000000000002366
|View full text |Cite|
|
Sign up to set email alerts
|

A 2018 Reference Guide to the Banff Classification of Renal Allograft Pathology

Abstract: The Banff Classification of Allograft Pathology is an international consensus classification for the reporting of biopsies from solid organ transplants. Since its initial conception in 1991 for renal transplants, it has undergone review every 2 years, with attendant updated publications. The rapid expansion of knowledge in the field has led to numerous revisions of the classification. The resultant dispersal of relevant content makes it difficult for novices and experienced pathologists to faithfully apply the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
481
0
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 579 publications
(556 citation statements)
references
References 27 publications
4
481
0
25
Order By: Relevance
“…Taking together, ci and ct allowed to semi-quantitatively grade IF/TA according to Banff classification: grade I, mild (ci1 or ct1); grade II, moderate (ci2 or ct2); and grade III, severe (ci3 or ct3). 2 To improve accuracy of interstitial fibrosis evaluation, renal biopsy sections (3 µm) were stained with Sirius red. Sirius red specifically stains collagen fibres.…”
Section: Histopathological Analysis Of Renal Fibrosismentioning
confidence: 99%
“…Taking together, ci and ct allowed to semi-quantitatively grade IF/TA according to Banff classification: grade I, mild (ci1 or ct1); grade II, moderate (ci2 or ct2); and grade III, severe (ci3 or ct3). 2 To improve accuracy of interstitial fibrosis evaluation, renal biopsy sections (3 µm) were stained with Sirius red. Sirius red specifically stains collagen fibres.…”
Section: Histopathological Analysis Of Renal Fibrosismentioning
confidence: 99%
“…Histologic findings remain the key element for the diagnosis of T cell–mediated rejection (TCMR) and antibody‐mediated rejection (ABMR) in kidney transplantation. According to the Banff classification, peritubular capillaritis (ptc), glomerulitis (g), interstitial inflammation (i), and tubulitis (t) constitute the main pathologic features of kidney allograft rejection and are characterized by the presence of “mononuclear cells” within peritubular capillaries, glomeruli, interstitium, and tubules respectively. Thus far, it is not recommended to specify the exact phenotype of these immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important study question as subclinical inflammation because of its chronic low‐grade nature is not promptly diagnosed and can facilitate delayed allograft dysfunction. The authors recruited three patients who demonstrated such inflammation (Banff i‐ and t‐ < 2) on their 6 months post‐transplant biopsy. Patients were already on MMF, tacrolimus and prednisolone when they had their Treg cells acquired.…”
Section: Clinical Trials: Today and Tomorrowmentioning
confidence: 99%